Colonial Museology and Coloniality of Knowledge in Malaya - Abd Jalal, Ahmad Farid; Awang Pawi, Awang Azman; Abd Rahim, Rahimin Affandi (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2026)
This article examines the relationship between Western colonial museology and the coloniality of knowledge in the Malay World, with particular attention to natural history museums, colonial anthropology, and British scientific imperialism. The study adopts a qualitative approach grounded in historical textual analysis and critical historiography of historiographical sources, colonial documents, critical museology scholarship, and the history of colonial science. The findings show that the development of modern museums was closely intertwined with Western imperialism, the production of scientific knowledge, and the construction of colonial epistemic authority over local societies and tropical environments. In the Malay Peninsula, institutions such as the Perak Museum developed as part of British administrative science that facilitated the collection of local flora, fauna, minerals, and ethnographic data in the interests of colonial economic and administrative concerns. The study further shows that modern scientific institutions such as FRIM and IMR emerged from the broader structure of colonial scientific imperialism. At the same time, the article argues that epistemic coloniality continues to persist within post-colonial museum institutions through the continuity of Western classificatory systems and curatorial approaches. Nevertheless, the emergence of Malay-Islamic museology in Malaysia reflects ongoing efforts to reconstruct local epistemologies by incorporating Jawi manuscripts, Malay-Islamic civilization, intellectual traditions, and the Islamic worldview into contemporary museum narratives.